Building climate resilience through nexus thinking - McCartney, Matthew P.; Ringler, Claudia (CGIAR System Organization, 2024)
There has been little time to rest between the two COPs. The biodiversity COP16 conference generated limited, but important, progress in negotiations and a surge of energy among biodiversity advocates. Now we are immersed in the climate change COP29 conference in Azerbaijan, with hopes for significant progress. Both these events starkly highlight the interconnected crises we face in the biosphere, atmosphere, and hydrosphere and underscore the urgency of adopting water–energy–food–ecosystems (WEFE) nexus approaches; the connections have never been clearer. In Colombia, at COP16, NEXUS Gains contributed to many events – see below – under the conference’s encompassing theme of “Peace with Nature”. This theme captures the essence of WEFE nexus approaches, which aim to reconcile competing needs and ensure harmonious, sustainable outcomes. As we shift our focus to COP29, a critical question emerges: can we make peace with the climate? Nexus approaches and their practitioners have valuable insights to share and we look forward to contributing to that critical conversation.